Targeted micro-health insurance in the Department of Nouna, Burkina Faso - Schleicher, Michael (2017)
While antipoverty programs become increasingly popular in low-income countries, they often fail to adequately cover the poor. This dissertation considers a voluntary micro-health insurance scheme in Burkina Faso, which has applied community-based targeting to offer poor households a premium discount. It addresses two main reasons for low program coverage in low-income countries, inaccurate targeting of poverty programs and low take-up by the poor. The empirical analysis rests on the combination of four different micro-datasets and follows three different approaches to program evaluation. The main findings from this dissertation are as follows. First, community-based targeting targets consumption-poor households fairly accurately when compared to four statistical targeting methods. Furthermore, for common transfer amounts it is by far the most cost-effective method. Second, the community-based targeting decision exhibits a moderate but highly statistically significant allocations bias due to ethnic favoritism. Third, the 50 percent premium subsidy in this context is successful in increasing health insurance demand among moderately poor urban households but is ineffective for very poor rural households.
Enthält 4 Beiträge
Keywords: Hochschulschrift